Technology Acceptance Model on Gojek Applications in Purwokerto - Yohanes Febri Widianto; Haryadi .; Devani Laksmi Indyastuti (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
This research is a quantitative study on the application of Gojek in Purwokerto. The purpose of this study was to analyze the acceptance of Gojek applications in Purwokerto using the Technology Acceptance Model. This study uses the Structural Equation Modeling analysis method using the SmartPLS3 application. The results of the analysis show that (1) Perceived ease of use has a positive effect on perceived usefulness, (2) Perceive usefulness is not significant and has a negative effect user attitudes, (3) Perceived ease of use has a positive effect on user attitudes, (4) Quality has a positive effect on user attitudes,(5) Perceived usefulness is not significant and has a negative effect on behavior to use, (6) User attitude positively effect behavior to use.